Mouse Mesenchymal Progenitor Cells Expressing Adipogenic and Osteogenic Transcription Factors Suppress the Macrophage Inflammatory Response - Natalie Fernandez; Heather Renna; Lauren McHugh; Katie Mazolkova; William Crugnola; Jodi F. Evans (Stem Cells International)
Mesenchymal progenitor cell characteristics that can identify progenitor populations with specific functions in immunity are actively being investigated. Progenitors from bone marrow and adipose tissue regulate the macrophage (MΦ) inflammatory response by promoting the switch from an inflammatory to an anti-inflammatory phenotype. Conversely, mesenchymal progenitors from the mouse aorta (mAo) support and contribute to the MΦ response under inflammatory conditions. We used cell lines with purported opposing immune-regulatory function, a bone marrow derived mesenchymal progenitor cell line (D1) and a mouse aorta derived mesenchymal progenitor cell line (mAo). Their interaction and regulation of the MΦ cell response to the inflammatory mediator, lipopolysaccharide (LPS), was examined by coculture. As expected, D1 cells suppressed NO, TNF-α, and IL-12p70 production but MΦ phagocytic activity remained unchanged. The mAo cells enhanced NO and TNF-α production in coculture and enhanced MΦ phagocytic activity. Using flow cytometry and PCR array, we then sought to identify sets of MSC-associated genes and markers that are expressed by these progenitor populations. We have determined that immune-supportive mesenchymal progenitors highly express chondrogenic and tenogenic transcription factors while immunosuppressive mesenchymal progenitors highly express adipogenic and osteogenic transcription factors. These data will be useful for the isolation, purification, and modification of mesenchymal progenitors to be used in the treatment of inflammatory diseases.